EFFECTIVENESS OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) THERAPY ON MENTAL HEALTH IN ADOLESCENTS: A LITERATURE REVIEW - Putri Keke Yuni Nursa’at; Nur Khasanah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Mental health is influenced by the balance of psychological, emotional, and spiritual aspects. One emerging spiritual-based non-pharmacological intervention is the Spiritual Emotional Freedom Technique (SEFT), a tapping technique on energy points accompanied by affirmations and prayers. This study aims to assess the effectiveness of SEFT on stress, anxiety, and depression. The method used was a systematic literature review of articles published between 2021 and 2025 in the Scopus and Google Scholar databases, with human populations and quantitative outcomes. The literature search was conducted using a combination of keywords in Indonesian (SEFT, stress, anxiety, depression, mental health) and English (SEFT, stress, anxiety, depression, mental health). Of the 16,712 identified articles, a selection process was conducted based on the 2020 PRISMA guidelines through the stages of identification, screening, eligibility, and inclusion. Five articles met the inclusion criteria for review and critical analysis. The results showed that most studies reported significant reductions in stress, anxiety, and/or depression after the SEFT intervention, using instruments such as the DASS-21, HADS, and PSS. SEFT has the potential to be a non-pharmacological spiritual intervention to support psychological well-being and holistic nursing practice, although large-scale RCTs with more robust methodological designs are needed.